Formalisation and reuse of cost engineering knowledge - Rush, C. (Cranfield University, 2002)
This thesis is concerned with understanding the role and utilisation of cost engineering knowledge for generating cost estimates with respect to long life cycle, complex hardware products. lt examines whether there is a formal structure to the reasoning process of experts as they use judgement and whether this process can be represented within a model. The aim is to develop a framework that formalises cost engineering knowledge to facilitate its reuse. A literature review examines the role of expert knowledge and judgement for generating cost estimates. The review identifies that there are mixed views on how knowledge is used and managed. Using an industrial case study approach, the author identifies the cost estimation practices for a new military air system. The study establishes that it is essential to capture assumptions and associated rationale to facilitate knowledge reuse. Experts use an analogy based reasoning process to make judgments and assumptions. The reasoning process became the focus of detailed studies using experts from across industry, resulting in a generic model. The model, known as an inference structure, was implemented within a software tool. This provided a formalised framework to represent, capture, and reuse assumptions and associated rationale. The thesis concludes that assumptions and rationale need to be captured during the development of cost estimates to facilitate knowledge reuse. There is a formal, generic reasoning process that experts use when applying their judgement. The results provide industry with a structured, consistent approach to the formalisation and reuse of cost engineering knowledge. By adopting this approach, companies can develop consistent estimates that will in turn improve decision-making across industry.